STUDI PUSTAKA TENTANG ASPEK KEPEMIMPINAN DILIHAT DARI PERBEDAAN JARAK DAN KEKUASAAN DALAM SUKSESI BISNIS MILIK KELUARGA - Anita Maharani (Jurnal Universitas Paramadina, 2013)
AbstractLeadership is an important issue for any kinds of organization, including Family Owned Enterprise (FOE). FOE is a business that established by family, run by family, and usually continued through generations by family. Furthermore, leadership in FOE becomes more important when it needs to be passed from one generation to another or so called a succession. However, since FOE is a unique organization, its leadership aspects should be unique. This article describes a leadership model that explains the leader-follower relationship in FOE setting. It also discusses the leadership style differences between male and female based on literature perspectives.Keywords: leadership, succession, family, owned, enterprise.